IMPROVING STUDENT CRITICAL THINKING SKILLS IN SOCIAL SUBJECT THROUGH THINK PAIR SHARE DISCUSSION METHOD - Carinih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Learning methods applied in schools are still conventional, which limits the development of students' abilities and skills. This study aims to improve students’ critical thinking skills through the Think-Pair-Share learning method. The research was conducted on class VII.2 at SMPN 5 Singingi, involving 24 students. The research design used was classroom action research. The instruments included teacher and student action observation sheets and a critical thinking skills test. The results showed that teacher actions in the first cycle reached 72% (quite good), increasing to 83% (good) in the second cycle. Student activity improved from 75% (sufficient) in the first cycle to 88% (good) in the second cycle. Meanwhile, students’ critical thinking skills increased from 65% (good) in the first cycle to 77% (good) in the second cycle. Based on these findings, it can be concluded that the Think-Pair-Share method can effectively improve the critical thinking skills of students in class VII.2 at SMPN 5 Singingi.